Refusal of Assent – A Hidden Element of Constitutional History in New Zealand - Martin, John E (Victoria University of Wellington Law Review, 2010)
This article explores Britain's influence historically over legislation passed in the New Zealand Parliament. It suggests that Britain's role was substantial, particularly in the 19th century. For nearly a century, from 1854 until New Zealand adopted the Statute of Westminster in 1947, all New Zealand laws (of which nearly one hundred laws were reserved) were sent to Britain for scrutiny. In thirteen instances laws were considered sufficiently problematic that Britain either disallowed legislation already assented to by the Governor or, alternatively, refused assent to or withheld assent from reserved legislation. Other legislation was amended on Britain's instructions. The exercise of royal assent was an important ingredient in New Zealand's development and an integral part of its movement from colony to independent nation.